Enhanced fertility and chill tolerance after cold-induced reproductive arrest in females of temperate species of the Drosophila buzzatii complex - Mensch, Julian (2017)
Long-term exposure to low temperatures during adult maturation might decrease fertility after cold recovery as a consequence of carryover effects on reproductive tissues. This pattern should be more pronounced in tropical than in temperate species as protective mechanisms against chilling injuries are expected to be more effective in the latter. We initially determined the lower thermal thresholds to induce ovarian maturation in four closely related Drosophila species, two inhabiting temperate regions and the other two tropical areas of South America. As expected, only temperate species regularly experience cold-inducing conditions for reproductive arrest during winter in their natural environment. Subsequently, we exposed reproductively arrested and mature females to cold-inducing conditions for reproductive arrest over a long period. Following cold exposure, tropical species exhibited a dramatic fertility decline, irrespective of reproductive status. In contrast, not only were temperate females fecund and fertile but also fertility was superior in females that underwent cold-induced reproductive arrest, suggesting that it might act as a protecting mechanism ensuring fertility after cold recovery. Based on these findings, we decided to evaluate the extent to which reproductive status affects cold tolerance and energy metabolism at low temperature. We found a lower metabolic rate and a higher cold tolerance in reproductively arrested females, although only temperate species attained high levels of chill tolerance. These findings highlight the role of cold-induced reproductive arrest as part of an integrated mechanism of cold adaptation that could potentially contribute to the spread of temperate species into higher latitudes or altitudes.